DIFFUSION-INNOVATION THROUGH VISUAL COMMUNICATION OF TRUCK BACK PAINTINGS IN THE COMMUNITY TRUCK OF MALANG (KTM) - Pratama, Nicholas Wila Adi; Swandi, I Wayan; Udayana, Anak Agung Gede Bagus; Artadi, I Made Pande (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
The phenomenon of truck bed painting has encouraged the author to further recognize it through field research conducted personally between 2016 and 2017 through the holding of a truck modification contest held by the Malang Truck Community (KMT). Currently, the community has implemented digital printing techniques as a new technique that has never been used by other artists or other truck communities. The visualization technique that was initially painted manually has now shifted to digital printing techniques that have succeeded in cutting costs to be cheaper, faster in the process, increasing the number of orders every day. The research question is how does diffusion-innovation occur in truck bed painting? The purpose of the research is to describe in detail the results of the study of diffusion and innovation that describe the tendency to use elements typical of local culture in truck bed visuals and create works of art that become an integral part of the identity of the community that uses them. Qualitative research methods using data collection techniques through in-depth interviews, observations, and visual analysis as well as deepening other relevant findings. Then determine the research participants, such as truck artists, truck owners, members of the Malang Truck Community (KTM) or local communities. Selecting a representative sample that covers various aspects of visual innovation in the context of the development of truck painting art. The results of the study found that there had been a process of innovation diffusion in truck bed painting art in the Malang Truck Community (KTM) where through visual aspects it was able to communicate ideas, messages, and meanings that encouraged the spread of new technology, new ideas, and new policy perspectives in an area where the truck community carried out a sustainable creative process.